A ray of hope for a woman with Sheehan's syndrome. (4th February 2013) - Jain, Deepti
Abstract : A 25-year-old woman presented with a history of secondary amenorrhoea for the last 3 years, coinciding with her delivery. She delivered at home and had massive postpartum haemorrhage. She was brought in a state of circulatory collapse to the nearest teaching hospital, where she was resuscitated. She developed anaemia, septicaemia and extradural empyema. The complications were managed and the woman improved. Presently, she approached us for infertility. She was investigated and diagnosed with postpartum hypopituitarism, that is, Sheehan's syndrome. Her gonadotrophin levels, luteinising hormone/follicle-stimulating hormone, were normal, serum oestradiol was low and serum prolactin was also on the lower side. She had started with genital atrophy and was given three cycles of cyclic oestrogen +progesterone combination. Ovulation was induced. She conceived and her antenatal period was uneventful. She delivered a full-term baby vaginally. However, she had inadequate lactation after delivery and lost the baby at one-and-a-half months' age due to gastroenteritis.